AMIRI AND ZAVQI (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, the works of Amiriy and the poet Zavkiy, who founded the literary environment of Kokan, are studied. Attention is paid to the issues of literary influence, originality and skill of poets.